The effect of Self-Regulation Based Cognitive Psychoeducation Program on emotion regulation and self-efficacy in children diagnosed with attention deficit hyperactivity disorder - KARACA, SEMRA (My University, 2023)
Aim: This study aimed to determine the effect of Self-Regulation Based Cognitive Psychoeducation Program on emotion regulation and self-efficacy in children diagnosed with attention deficit hyperactivity disorder (ADHD) and receiving medication. Method: The sample of this study with control group and pre-test, post-test and follow-up randomized experimental design consisted of children followed in the child and adolescent mental health outpatient clinic of a state hospital. The data were evaluated by parametric and non-parametric analyses. Results: A statistically significant increase was determined in the internal functional emotion regulation mean scores of children, who participated in the Self-Regulation Based Cognitive Psychoeducation Program, measured before, immediately after, and 6 months after the intervention (p < 0.05). A statistically significant increase was also found in their external functional emotion regulation mean scores measured before and 6 months after the intervention (p < 0.05). In addition, a statistically significant difference was found between their internal dysfunctional and external dysfunctional emotion regulation mean scores measured before and 6 months after the intervention; however the mean scores of those in the control group 6 months after the intervention were higher than those in the intervention group (p < 0.05). Furthermore, there was a statistically significant increase in their self-efficacy mean scores measured before and 6 months after the intervention (p < 0.05). Conclusion: The Self-Regulation Based Cognitive Psychoeducation Program was found be effective in increasing the levels of emotion regulation and self-efficacy in children with ADHD.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Psikiyatri; Clinical Medicine (MED); PSYCHIATRY; Psikiyatrik Ruh Sağlığı; Psychiatric Mental Health; Emotion regulation; Self-efficacy; Self-Regulation Based Cognitive Psychoeducation Program; Self-Regulation Based Cognitive; Psychoeducation Program; Emotion regulation; Self-efficacy